A radial basis function artificial neural network model for water quality evaluation - GUO Zong-lou (浙江大学学报. 农业与生命科学版)
A model for water quality evaluation is constructed by using a radial basis function artificial neural network (RBF-ANN), and trained by using a least squares estimation algorithm. The results related to water quality evaluation for a reservoir show that it is possesses reasonability, objectivity, generality and practicability on water quality evaluation by using RBF-ANN in cooperation with the RBF-LS algorithm.